Aspek Lokalitas Tafsir Fai al-Rahman Karya Muhammad Sholeh Darat - Mohamad Zaenal Arifin (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2018)
The birth of exegesis literature and Qurâ€™an translation in the local language is a response of and an influence from the socio-cultural background of mufassir. It is understandable considering that exegesis of the Qurâ€™an was a result of mufassirâ€™s intellectual construction explaining messages of God in the Qurâ€™an taking into account human needs in a particular social and cultural environment including with its surrounding complex values. In this case, the researcher is interested in Tafsir Fayá¸ al-Raá¸¥mÄn written by Kiai Sholeh Darat, for it was a fact of the prevailing internalization of Javanese culture into Islam which creates a collaboration pattern between a specific Javanese culture and Islam and becomes a particular phenomenon in terms of tafsÄ«r al-Qurâ€™Än. Several reasons underlie Kiai Sholeh Darat to undertake intellectual preaching to people by writing works in local language. First, the social and political conditions in last 19th Century show that that majority of Javanese people are Muslims who are unfamiliar with religious understanding. Second, in that condition, Java was under control of colonial governor that supervised and restricted Kiai Saleh Darat preaching.